Effect of Lockdown on HCHO and Trace Gases over India during March 2020 - Akshansha Chauhan; Ramesh P. Singh (Aerosol and Air Quality Research)
Abstract COVID-19 is one of the deadly Epidemics that has impacted people living in more than 200 countries. In order to mitigate the impact of COVID-19, India observed total lockdown in the first phase for a period of 21 days (24 March–13 May 2020), so that social distancing is maintained. However, this sudden decision severely affected the normal life of people. The air quality improved due to lockdown, some relaxation was given in different cities and within some areas in the city where the people were not affected by COVID-19. In this paper, we discuss results of detailed analysis of trace gases (HCHO, NO2, SO2, CH4, CO and O3) and particulate matter concentration using satellite and ground data in major metropolitan cities of India during 10–31 March, 2020 and compared with the same period in the year 2019, to study the impact of total lockdown. Our analysis suggests, pronounced qualitative changes in HCHO, NO2, SO2, CH4, CO, O3 and PM2.5 concentration during complete lockdown period in the month of March 2020. We did not consider the period after 31 March 2020 to avoid influence of anthropogenic sources since the Government made relaxation in the lockdown periods after 31 March 2020.